2011
DOI: 10.1002/polb.22274
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of porous crosslinked polymers with different surface morphologies via chemically induced phase separation

Abstract: A novel and simple method for producing crosslinked polymers with controlled surface morphology is demonstrated in this study. The porous crosslinked polymers were made via stepwise polymerization of a mixture of epoxy resin, D.E.R. 331, and diethylene triamine in diisobutyl ketone (DIBK). Both the surface and bulk morphology of the cured polymers are dependent on the solvent fraction of the reactive solution. When the concentration of DIBK was more than about 30 vol %, chemically induced phase separation (CIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Most oen, the domains of the organic solvent are removed aer the RIPS process has completed, which can be used to create porous crosslinked polymers. [9][10][11] In comparison, the phase evolution of photoinduced crosslinking during simultaneous solvent evaporation has been studied scarcely. Guenthner et al showed that RIPS in evaporative solvents can yield sparse three-dimensional networks without signicant structural collapse, which is characteristic for RIPS in non-evaporative solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Most oen, the domains of the organic solvent are removed aer the RIPS process has completed, which can be used to create porous crosslinked polymers. [9][10][11] In comparison, the phase evolution of photoinduced crosslinking during simultaneous solvent evaporation has been studied scarcely. Guenthner et al showed that RIPS in evaporative solvents can yield sparse three-dimensional networks without signicant structural collapse, which is characteristic for RIPS in non-evaporative solutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, under the silicone (OPP) contacting film, the surface pore size and porosity of the membranes are approximately 1.44 and 0.45 μm, respectively. The difference of interfacial tension of the solid/solvent‐rich phase and solid/polymer‐rich phase could significantly influence the phase separation process among the interfaces of solid and liquid solutions, and it will cause the different surface morphologies . Therefore, it was suggested that different surface morphologies of epoxy membranes with similar bulk structures can be prepared using CIPS with different contacting films.…”
Section: Resultsmentioning
confidence: 99%
“…There are many techniques for controlling the surface morphology of a membrane, such as surface treatment, surface grafting polymerization, templating, or self‐assembly methods, which have been applied to produce specific surface structures on polymer films . We also demonstrated a novel, simple method for producing porous cross‐linked polymers that have similar bulk morphologies and a variety of surface structures through the use of a CIPS process . The surface morphology could be changed with the use of contacting films with different wetting properties, which were pressed onto the casting solution during curing.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, there are many techniques for making porous membranes and to tune morphology through polymer solution phase inversion, such as non-solvent induced phase separation (NIPS) [21,22], thermally induced phase separation (TIPS) [23,24], vapor induced phase separation (VIPS) [25,26], polymerization reaction [27] and cryogenic processes [28]. It is difficult to prepare membranes with nanoscale pores using these conventional approaches because phase inversion processes such as non-solvent introduction or thermal influence often fix the polymer chains in such a short time that they cannot adjust their configuration to approach one another sufficiently closely.…”
Section: Introductionmentioning
confidence: 99%